The impact of mobile digital technology on influencing behavior / W. Hutchinson and A. Jones - Hutchinson, W.; Jones, A. (Centre for Media and Information Warfare Studies, 2008)
This speculative paper examines both the present and future uses of ubiquitous, mobile digital technologies to propagandise, deceive, behaviour modification and influence. These individualised technologies have the potential for both generic and individual targeting of those to be influenced. The techniques used and success will depend on both the time span available which would determine whether the objective is to coerce, manipulate or convert the target(s) and what stage the persuasive process has reached. Speculation on the impact of developing peripherals that expand the human sensory experience and produce an overall real time virtual environment is carried out. The issues of the impact on ubiquitous personalised communications on social impact, privacy, security, and behaviour modification are examined.